2002
DOI: 10.1108/09649420210433175
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in ethical decision making

Abstract: Most of the research on fostering ethical climates by making ethical decision choices in organisations has taken place in the last 20 years. Research has moved from specific studies evaluating either individual or situational variables as factors in ethical decision behaviour to more complex models that encompass the interaction of individual and situational factors. This study revisits the influence of the individual variable of gender on ethical decision making. Using a laboratory format and decision exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 35 publications
6
81
0
3
Order By: Relevance
“…Gender-related value differences were larger in the older group. In workplace values, on the other hand, Glover et al (2002) found no significant difference between women and men. The fact that women and men hold different values has no bearing on finding out about the values in the foreign location.…”
Section: Hypothesis 2a: Female Expatriates Have Lower Cognitive Confimentioning
confidence: 58%
“…Gender-related value differences were larger in the older group. In workplace values, on the other hand, Glover et al (2002) found no significant difference between women and men. The fact that women and men hold different values has no bearing on finding out about the values in the foreign location.…”
Section: Hypothesis 2a: Female Expatriates Have Lower Cognitive Confimentioning
confidence: 58%
“…First, there are hypothesized differences in male and female communication and ethical decision making. 38,39 Second, we wanted a sample that was homogeneous to prevent unexplainable results, because previous authors 18,40 have acknowledged that more evidence is needed to support a lack of gender differences in critical-thinking behaviors, so we followed the procedures cited in previous research. However, female certified athletic trainers should be considered in future investigations to provide a better understanding of all athletic trainers.…”
Section: Limitationsmentioning
confidence: 99%
“…Minor differences have also been detected in the moral reasoning of men and women. For example, women may be more likely to make ethical choices (Glover, Bumpus, Sharp, & Munchus, 2002) and reason on the basis of care rather than justice (Jaffee & Hyde, 2000;Wark & Krebs, 1996).…”
Section: How Extraneous Factors Affect Moral Judgmentmentioning
confidence: 99%